Biogenic polymeric materials from lignocellulosic biomass-derivable 4-pentenoic acid and isosorbide for potential biomedical applications - Döpping, Daniel; Kern, Johann; Rotter, Nicole; Llevot, Audrey; Mutlu, Hatice (ACS sustainable chemistry & engineering, 2024)
The increasing substitution of petroleum-based polymers with materials of biogenic origin is an important step towards the desired circular economy. In fact, research in this area is not only leading to CO2-neutral polymers but is also enabling the development of completely new materials with cell compatibility. Thus, by using the toolbox of lignocellulosic biomass derivatives (in particular, isosorbide and 4-pentenoic acid; the latter being less explored and recognized in the field of synthetic polymer chemistry), acyclic diene metathesis polymerization has been explored for the synthesis of the biogenic polymer derivative. Upon characterizing the chemical structure of the 100% “biomass-derived” polyester derivative by nuclear magnetic resonance (NMR), size exclusion chromatography (SEC), and attenuated total reflectance infrared (ATR-IR) spectroscopy, we have explored the thermal properties via thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The DSC study has revealed that the polymer exhibits a glass transition temperature (Tg) value of 17 °C, thus reflecting an amorphous behavior. The mechanical properties and cell compatibility of the polyester derivative were also evaluated by dynamic mechanical analysis (DMA) and a cytotoxicity test. By assessing the cytotoxicity of the functional novel polyester derivative, we were able to reflect the benefit of employing isosorbide and 4-pentenoic acid as building blocks for materials with potential biomedical applications (in particular, as a new cartilage material).
Online veröffentlicht: 28. August 2024
Gesehen am 16.10.2024